2018
DOI: 10.3390/en11092256
|View full text |Cite
|
Sign up to set email alerts
|

Quota Allocation for Carbon Emissions in China’s Electric Power Industry Based Upon the Fairness Principle

Abstract: As an essential measure to mitigate the CO2 emissions, China is constructing a nationwide carbon emission trading (CET) market. The electric power industry is the first sector that will be introduced into this market, but the quota allocation scheme, as the key foundation of market transactions, is still undetermined. This research employed the gross domestic product (GDP), energy consumption, and electric generation data of 30 provinces from 2001 to 2015, a hybrid trend forecasting model, and a three-indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Some scholars contend that historical carbon emissions have inflicted considerable harm on the environment, and the emitters should be accountable for their actions. Therefore, provinces with higher historical emissions should be allocated fewer carbon allowances (Pan, 2014a;Wei et al, 2014;Meng, 2018;Wang et al, 2018;Kong, 2019). However, other scholars maintain that the principle of the "grandfather law" should serve as the foundation for allocation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars contend that historical carbon emissions have inflicted considerable harm on the environment, and the emitters should be accountable for their actions. Therefore, provinces with higher historical emissions should be allocated fewer carbon allowances (Pan, 2014a;Wei et al, 2014;Meng, 2018;Wang et al, 2018;Kong, 2019). However, other scholars maintain that the principle of the "grandfather law" should serve as the foundation for allocation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding historical emissions, there are two opposing viewpoints. One school of thought maintains that the higher the level of historical emissions, the greater the responsibility for carbon emission reduction, justifying the allocation of fewer carbon allowances (Wei et al, 2013;Pan, 2014b;Meng, 2018;Wang et al, 2018;Kong, 2019); while another advocates for grandfathering, whereby a larger quantity of historical emissions warrants an increase in carbon allowances (Zhou et al, 2023;Ye et al, 2019;Schmidt and Heitzig, 2014;Zhou, 2013;Shi et al, 2012;Goulder et al, 1999). The economic strength of each province is reflected in its ability to pay, which determines the extent to which emissions can be reduced.…”
Section: Design Of Carbon Quota Allocation Schemementioning
confidence: 99%
“…The above situation can be corrected by the development of the market mechanisms for the sale of emissions of harmful substances by the power plants [47][48][49]. Based on this market, the initially allocated quotas for pollutants and greenhouse gases will be redistributed from a position of minimizing total costs.…”
Section: Analysis Of the Market Formation For Emissions Quotas Of Thementioning
confidence: 99%
“…The electric power industry is the first sector that was introduced into the Carbon Emissions Trading market, which is being constructed in China. Meng et al [21] utilized a hybrid trend forecasting model and a three-indicator allocation model to propose a quota allocation scheme for carbon emissions in China's electric power industry in 30 provinces from 2016 to 2030. The research findings indicated that nine provinces are expected to be the buyers in the Carbon Emissions Trading market.…”
Section: Quotas Allocation For Carbon Emissionsmentioning
confidence: 99%